Enzyme replacement therapy for Fabry disease: some answers but more questions - Majid Alfadhel; Sandra Sirrs (Dove Medical Press, 2011)
Majid Alfadhel1, Sandra Sirrs21Division of Biochemical Diseases, Department of Paediatrics, BC Children’s and Women’s Hospital, University of British Columbia, Vancouver, BC, Canada; 2Adult Metabolic Diseases Clinic, Division of Endocrinology, Department of Medicine, Vancouver Hospital and Health Sciences Centre, University of British Columbia, Vancouver, BC, CanadaAbstract: Fabry disease (FD) is a multisystem, X-linked disorder of glycosphingolipid metabolism caused by enzyme deficiency of α-galactosidase A. Affected patients have symptoms including acroparesthesias, angiokeratomas, and hypohidrosis. More serious manifestations include debilitating pain and gastrointestinal symptoms, proteinuria and gradual deterioration of renal function leading to end-stage renal disease, hypertrophic cardiomyopathy, and stroke. Heterozygous females may have symptoms as severe as males with the classic phenotype. Before 2001, treatment of patients with FD was supportive. The successful development of enzyme replacement therapy (ERT) has been a great advancement in the treatment of patients with FD and can stabilize renal function and cardiac size, as well as improve pain and quality of life of patients with FD. In this review, we have provided a critical appraisal of the literature on the effects of ERT for FD. This analysis shows that data available on the treatment of FD are often derived from studies which are not controlled, rely on surrogate markers, and are of insufficient power to detect differences on hard clinical endpoints. Further studies of higher quality are needed to answer the questions that remain concerning the efficacy of ERT for FD.Keywords: Fabry disease, agalsidase α, agalsidase β, Replagal, Fabrazyme, critical appraisal, evidence-based medicine